THE INFLUENCE OF COMPENSATION AND SOCIAL SECURITY ON EMPLOYEE WORK MOTIVATION AT PT. PERMODALAN NASIONAL MADANI LAMPUNG BRANCH - Qasas, Arman Al; Pratikno, Yuni; Jati, Prihatina (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
Using a simple random sampling technique, a sample of 40 PT employees was taken. Lampung Branch Civil National Capital The tcount value of the compensation variable (X1) is 4,067 while the ttable value for n = 40 is 2,021. So 4,067 > 2,021, then H0 is rejected and Ha is accepted, it is stated that compensation (X1) has an effect on work motivation (Y). Compensation has a significant influence on employee work motivation. The tcount value for the Social Security variable (X2) is 4.067, while the ttable value for n = 40 is 2.021. So 4,067 > 2,021, then H0 is rejected and Ha is accepted, it is stated that compensation (X1) has a positive effect on work motivation (Y). From the results of the analysis in the table above, namely the ANOVA test, the Fcount value was 42,098, while the Ftable ( 0.05) for n = 40 was 2.84. So Fcount > from Ftable ( 0.05) or 42,098 > 2.84 with a significance level of 0.000 or 0.000 < 0.05, then it can be said that compensation (X1) and social security (X2) are jointly related to work motivation (Y). Based on the table above, a relationship test was carried out for the three variables, and based on the Model Summary table, an R value of 0.695 was produced. This shows that 69.5% of compensation (X1) and social security (X2) are simultaneously related to work motivation (Y) while the remaining 30.5% is related to other factors not examined in this research. Taken together, compensation and social security have a significant influence on work motivation. The combination of the two creates a work environment that supports the basic needs and appreciation of employees.